Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

Adjusting the Structure and Electronic Properties of Carbons for Metal‐Free Carbocatalysis of Organic Transformations - Antonietti, Markus; Lopez Salas, Nieves; Primo, Ana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Influence of sp3/sp2-carbon ratio of vertically standing carbon nanostructures produced by pulsed laser-treatment on PAN-based carbon fibers - Engelkemeier, Katja; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Mimicking synaptic plasticity and learning behaviours in solution processed SnO2 memristor - Pan, Ying; Wan, Tao; Du, Haiwei; Qu, Bo; Wang, Danyang; Ha, Tae-Jun; Chu, Dewei (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Machine learning and natural language processing on the patent corpus: Data, tools, and new measures - Balsmeier, Benjamin; Assaf, Mohamad; Chesebro, Tyler; Fierro, Gabe; Johnson, Kevin; Johnson, Scott; Li, Guan‐Cheng; Lück, Sonja; O'Reagan, Doug; Yeh, Bill; Zang, Guangzheng; Fleming, Lee (Journal of Economics & Management Strategy)
Drawing upon recent advances in machine learning and natural language processing, we introduce new tools that automatically ingest, parse, disambiguate, and build an updated database using U.S. patent data. The tools identify unique inventor, assignee, and location entities mentioned on each granted U.S. patent from 1976 to 2016. We describe data flow, algorithms, user interfaces, descriptive statistics, and a novelty measure based on the first appearance of a word in the patent corpus. We illustrate an automated coinventor network mapping tool and visualize trends in patenting over the last 40 years.
Keywords: Management of Technology and Innovation; Strategy and Management; Economics and Econometrics; General Business; Management and Accounting; General Medicine

Effectuation, entrepreneurs' leadership behaviour, and employee outcomes: a conceptual model - Hubner-Benz, Sylvia; Baum, Matthias (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Internet of Things Architecture for Handling Stream Air Pollution Data - Kersting, Joschka; Geierhos, Michaela; Jung, Hanmin; Kim, Taehong (Proceedings of the 2nd International Conference on Internet of Things, Big Data and Security)
In this paper, we present an IoT architecture which handles stream sensor data of air pollution. Particle pollution is known as a serious threat to human health. Along with developments in the use of wireless sensors and the IoT, we propose an architecture that flexibly measures and processes stream data collected in real-time by movable and low-cost IoT sensors. Thus, it enables a wide-spread network of wireless sensors that can follow changes in human behavior. Apart from stating reasons for the need of such a development and its requirements, we provide a conceptual design as well as a technological design of such an architecture. The technological design consists of Kaa and Apache Storm which can collect air pollution information in real-time and solve various problems to process data such as missing data and synchronization. This enables us to add a simulation in which we provide issues that might come up when having our architecture in use. Together with these issues, we state r easons for choosing specific modules among candidates. Our architecture combines wireless sensors with the Kaa IoT framework, an Apache Kafka pipeline and an Apache Storm Data Stream Management System among others. We even provide open-government data sets that are freely available.
Keywords: Wireless Sensor Network; Internet of Things; Stream Data; Air Pollution; DSMS; Real-time Data Processing

Reciprocation Effort Games - Polevoy, Gleb; de Weerdt, M.M. (Proceedings of the 29th Benelux Conference on Artificial Intelligence)
Keywords: interaction; reciprocation; contribute; shared effort; curbing; convergence; threshold; Nash equilibrium; social welfare; efficiency; price of anarchy; price of stability

Competition between Cooperative Projects - Polevoy, Gleb; de Weerdt, M.M. (Proceedings of the 29th Benelux Conference on Artificial Intelligence)
Keywords: agents; projects; contribute; shared effort game; competition; quota; threshold; Nash equilibrium; social welfare; efficiency; price of anarchy; price of stability

Predicting Early Warning Signals of Financial Distress: Theory and Empirical Evidence - Sievers, Sönke; Klobucnik, Jan; Miersch, David
This study proposes a simple theoretical framework that allows for assessing financial distress up to five years in advance. We jointly model financial distress by using two of its key driving factors: declining cash-generating ability and insufficient liquidity reserves. The model is based on stochastic processes and incorporates firm-level and industry-sector developments. A large-scale empirical implementation for US-listed firms over the period of 1980-2010 shows important improvements in the discriminatory accuracy and demonstrates incremental information content beyond state-of-the-art accounting and market-based prediction models. Consequently, this study might provide important ex ante warning signals for investors, regulators and practitioners.
Keywords: Financial distress prediction; probability of default; accounting information; stochastic processes; simulation

"A variational formulation for fuzzy analysis in continuum mechanics" - Mahnken, Rolf (Mathematics and Mechanics of complex systems)
In order to improve the credibility of modern simulation tools, uncertainties of different kinds have to be considered. This work is focused on epistemic uncertainties in the framework of continuum mechanics, which are taken into account by fuzzy analysis. The underlying min-max optimization problem of the extension principle is approximated by α-discretization, resulting in a separation of minimum and maximum problems. To become more universal, so-called quantities of interest are employed, which allow a general formulation for the target problem of interest. In this way, the relation to parameter identification problems based on least-squares functions is highlighted. The solutions of the related optimization problems with simple constraints are obtained with a gradient-based scheme, which is derived from a sensitvity analysis for the target problem by means of a variational formulation. Two numerical examples for the fuzzy analysis of material parameters are concerned with a necking problem at large strain elastoplasticity and a perforated strip at large strain hyperelasticity to demonstrate the versatility of the proposed variational formulation.
Keywords: fuzzy analysis; α-level optimization; quantities of interest; optimization with simple constraints; large strain elasticity; large strain elastoplasticity

Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing - Kimotho, James Kuria; Sextro, Walter; Hemsel, Tobias (IEEE Transactions on Reliability)
Piezoelectric transducers are used in a wide range of applications. Reliability of these transducers is an important aspect in their application. Prognostics, which involve continuous monitoring of the health of technical systems and using this information to estimate the current health state and consequently predict the remaining useful lifetime (RUL), can be used to increase the reliability, safety, and availability of the transducers. This is achieved by utilizing the health state and RUL predictions to adaptively control the usage of the components or to schedule appropriate maintenance without interrupting operation. In this work, a prognostic approach utilizing self-sensing, where electric signals of a piezoelectric transducer are used as the condition monitoring data, is proposed. The approach involves training machine learning algorithms to model the degradation of the transducers through a health index and the use of the learned model to estimate the health index of similar transducers. The current health index is then used to estimate RUL of test components. The feasibility of the approach is demonstrated using piezoelectric bimorphs and the results show that the method is accurate in predicting the health index and RUL.
Keywords: Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing

Predicting Early Warning Signals of Financial Distress: Theory and Empirical Evidence - Klobucnik, Jan; Miersch, David; Sievers, Sönke (SSRN Electronic Journal)
This study proposes a simple theoretical framework that allows for assessing financial distress up to five years in advance. We jointly model financial distress by using two of its key driving factors: declining cash-generating ability and insufficient liquidity reserves. The model is based on stochastic processes and incorporates firm-level and industry-sector developments. A large-scale empirical implementation for US-listed firms over the period of 1980-2010 shows important improvements in the discriminatory accuracy and demonstrates incremental information content beyond state-of-the-art accounting and market-based prediction models. Consequently, this study might provide important ex ante warning signals for investors, regulators and practitioners.
Keywords: Financial distress prediction; probability of default; accounting information; stochastic processes; simulation

Measuring and modeling salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
For almost three decades, the theory of visual attention (TVA) has been successful in mathematically describing and explaining a wide variety of phenomena in visual selection and recognition with high quantitative precision. Interestingly, the influence of feature contrast on attention has been included in TVA only recently, although it has been extensively studied outside the TVA framework. The present approach further develops this extension of TVA’s scope by measuring and modeling salience. An empirical measure of salience is achieved by linking different (orientation and luminance) contrasts to a TVA parameter. In the modeling part, the function relating feature contrasts to salience is described mathematically and tested against alternatives by Bayesian model comparison. This model comparison reveals that the power function is an appropriate model of salience growth in the dimensions of orientation and luminance contrast. Furthermore, if contrasts from the two dimensions are comb
Keywords: Salience; Visual attention; Bayesian inference; Theory of visual attention; Computational modeling; Inference; Object Recognition; Theories; Visual Perception; Visual Attention; Luminance; Perceptual Orientation; Statistical Probability; Stimulus Salience; Computational Modeling

Accounting quality in private firms during the transition towards international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska (Accounting in Europe)
We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.  Full Article  Figures & data References  Citations Metrics  Reprints & Permissions  PDF Abstract We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.
Keywords: private firms; accounting quality; development of accounting standards; IFRS-like standards; Slovenia

Process characteristics and load-bearing capacities of joints welded with elements for the application in multi-material design - Meschut, Gerson; Schmal, Christopher; Olfermann, Thomas (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Self-locking self-pierce riveting: a new self-pierce riveting technology for multi-material applications in lightweight car body structures - Sartisson, Vadim; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Combining a high-speed mechanical joining technique with the attachment of functional elements in automotive structures - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Flow drill screwing of fibre-reinforced plastic-metal composites without a pilot hole - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, Markus; Peters, K.; Taube, Alexander; Keller, Adrian; Hoyer, Kay-Peter; Niendorf, Thomas; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Duplex stainless steel fabricated by selective laser melting - Microstructural and mechanical properties - Hengsbach, Florian; Koppa, Peter; Duschik, Kristina; Holzweissig, Martin Joachim; Burns, Madison; Nellesen, Jens; Tillmann, Wolfgang; Tröster, Thomas; Hoyer, Kay-Peter; Schaper, Mirko (Materials & Design)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

The Game of Reciprocation Habits - Polevoy, Gleb; de Weerdt, M.M.; Jonker, C.M. (Proceedings of the 2016 European Conference on Artificial Intelligence)
Keywords: agents; action; repeated reciprocation; fixed; floating; network; Nash equilibrium; social welfare; price of anarchy; price of stability; convex combination

How to Complete Customer Requirements: Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Bäumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB))
One purpose of requirement refinement is that higher-level requirements have to be translated to something usable by developers. Since customer requirements are often written in natural language by end users, they lack precision, completeness and consistency. Although user stories are often used in the requirement elicitation process in order to describe the possibilities how to interact with the software, there is always something unspoken. Here, we present techniques how to automatically refine vague software descriptions. Thus, we can bridge the gap by first revising natural language utterances from higher-level to more detailed customer requirements, before functionality matters. We therefore focus on the resolution of semantically incomplete user-generated sentences (i.e. non-instantiated arguments of predicates) and provide ontology-based gap-filling suggestions how to complete unverbalized information in the user’s demand.
Keywords: Requirement refinement; Concept expansion; Ontology-based instantiation of predicate-argument structure

Fast and conspicuous? Quantifying salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Advances in Cognitive Psychology)
Particular differences between an object and its surrounding cause salience, guide attention, and improve performance in various tasks. While much research has been dedicated to identifying which feature dimensions contribute to salience, much less regard has been paid to the quantitative strength of the salience caused by feature differences. Only a few studies systematically related salience effects to a common salience measure, and they are partly outdated in the light of new findings on the time course of salience effects. We propose Bundesen’s Theory of Visual Attention (TV A) as a theoretical basis for measuring salience and introduce an empirical and modeling approach to link this theory to data retrieved from temporal-order judgments. With this procedure, TV A becomes applicable to a broad range of salience-related stimulus material. Three experiments with orientation pop-out displays demonstrate the feasibility of the method. A 4th experiment substantiates its applicability t
Keywords: salience; visual attention; Bayesian inference; theory of visual attention; computational modeling; Visual Attention; Computational Modeling; Inference; Judgment; Statistical Probability

Peripheral visual cues: Their fate in processing and effects on attention and temporal-order perception. - Tünnermann, Jan; Scharlau, Ingrid (Frontiers in Psychology)
Peripheral visual cues lead to large shifts in psychometric distributions of temporal-order judgments. In one view, such shifts are attributed to attention speeding up processing of the cued stimulus, so-called prior entry. However, sometimes these shifts are so large that it is unlikely that they are caused by attention alone. Here we tested the prevalent alternative explanation that the cue is sometimes confused with the target on a perceptual level, bolstering the shift of the psychometric function. We applied a novel model of cued temporal-order judgments, derived from Bundesen’s Theory of Visual Attention.We found that cue–target confusions indeed contribute to shifting psychometric functions. However, cue-induced changes in the processing rates of the target stimuli play an important role, too. At smaller cueing intervals, the cue increased the processing speed of the target. At larger intervals, inhibition of return was predominant. Earlier studies of cued TOJs were insensitive
Keywords: cueing; temporal-order judgements; theory of visual attention (TVA); peripheral cue; processing speed; stimulus encoding; prior entry; Attention; Cues; Face Perception; Judgment

Mechanical properties of an innovative shear-clinching technology for ultra-high-strength steel and aluminium in lightweight car body structures - Hörhold, Réjane; Müller, Martin; Merklein, Marion; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

Theory of Knowledge for Literature Reviews: An Epistemological Model, Taxonomy and Empirical Analysis of IS Literature - Schryen, Guido; Wagner, Gerit; Benlian, Alexander (International Conference on Information Systems (ICIS))
Literature reviews play an important role in the development of knowledge. Yet, we observe a lack of theoretical underpinning of and epistemological insights into how literature reviews can contribute to knowledge creation and have actually contributed in the IS discipline. To address these theoretical and empirical research gaps, we suggest a novel epistemological model of literature reviews. This model allows us to align different contributions of literature reviews with their underlying knowledge conversions - thereby building a bridge between the previously largely unconnected fields of literature reviews and epistemology. We evaluate the appropriateness of the model by conducting an empirical analysis of 173 IS literature reviews which were published in 39 pertinent IS journals between 2000 and 2014. Based on this analysis, we derive an epistemological taxonomy of IS literature reviews, which complements previously suggested typologies.
Keywords: Literature review; Research methods/methodology; Theory of knowledge

Zum Einfluss des didaktischen Designs auf das (motivationale) Erleben von Lehrveranstaltungen: Eine quantitative Fallstudie im Rahmen der Methodeneinführung in den Bildungswissenschaften - Goller, Michael (die hochschullehre)
Im Sinne eines Scholarship of Teaching and Learning wird in diesem Aufsatz die Neugestaltung einer eigenständig durchgeführten Lehrveranstaltung im Bereich der Forschungsmethoden empirisch untersucht. Die neugestaltete Lehrveranstaltung integriert sowohl direkt-instruktionale als auch kooperativ-offene Sitzungsformate und wird mit einer thematisch ähnlichen Lehrveranstaltung des Jahres 2012 verglichen, welche fast ausschließlich im Vorlesungsstil (direkt-instruktional) gehalten wurde. Im Mittelpunkt des Evaluationsvorhabens standen folgende Forschungsfragen: (1) Unterscheiden sich die summativen Evaluationen der Lehrveranstaltungen der Jahre 2012 und 2014 in den Variablen subjektiver Lernerfolg, Motivation zur selbstständigen Auseinandersetzung mit den Inhalten sowie Gesamteindruck des Seminars?, (2) Welchen Einfluss hat die Form der Sitzungsgestaltung (direkt-instruktional vs. kooperativ-offen) auf das Erleben von Kompetenz, Autonomie und sozialer Eingebundenheit?, (3) Welche Form der Sitzungsgestaltung wird von den Studierenden stärker akzeptiert? und (4) Welchen Einfluss hat die Form der Sitzungsgestaltung auf den subjektiven Lernerfolg der Studierenden? Empirisch zeigte sich, dass die neugestaltete Lehrveranstaltung des Jahres 2014 von den Studierenden in fast allen Variablen als lernwirksamer eingeschätzt wurde. Des Weiteren ergaben sich Hinweise, dass sich kooperativ-offene Sitzungsformate positiv auf motivationale Ausgangsbedingungen auswirken.
Keywords: Direkte Instruktion; Evaluation; Kooperatives Lernen; Methodenausbildung; Paderborn; Scholarship of Teaching and Learning

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska (Review of Accounting Studies)
We examine whether the mandated introduction of International Financial Reporting Standards (IFRS) is associated with the propensity to access the public rather than private debt market and the cost of debt. We use a global sample of public bonds and private loans and find that mandatory IFRS adopters are more likely, post-IFRS, to issue bonds than to borrow privately. We also find that mandatory IFRS adopters pay lower bond yield spreads, but not lower loan spreads, after the mandate. These findings are consistent with debt providers responding positively to financial reporting of higher quality and comparability, but only when there is a greater reliance on publicly available financial statements than private communication. Lastly, we document that the observed debt market benefits are concentrated in countries with larger differences between domestic GAAP and IFRS and are present even for EU countries that did not experience concurrent financial reporting enforcement or other institutional reforms. Overall, our study documents positive economic consequences around the mandated IFRS adoption for corporate debt financing and, in particular, for bond financing.
Keywords: Accounting regulation; IFRS; Accounting quality; Public and private debt markets; Cost of debt

Investigation on joint characteristics of laser beam welded press hardenable ultra-high strength steels with ferritic-martensitic and martensitic microstructure - Janzen, V.; Meschut, G.; Dahmen, M.; Poprawe, R.; Lindner, S.; Wagener, R.; Melz, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Development of a Testing Method for the Identification of Friction Coefficients for Numerical Modeling of the Shear-Clinching Process - Müller, Martin; Vierzigmann, Ulrich; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Global competition as well as social and scientific megatrends strongly influence the modern car manufacturing industry. One of the most important approaches is the implementation of lightweight constructions. Therefore, the usage of high performance materials with tailored properties gains importance. For safety-relevant components such as automotive passenger cells it is necessary to minimize deformation to reduce the risk of injury for the vehicle occupants during a car accident. Thus, hot stamped high-strength steels have been established. High-strength and low formability of this kind of materials represent new challenges for joining technologies. One possibility to join high-strength steels is the newly developed shear-clinching technology. Due to the use of a combined cutting and joining process, the connection of dissimilar materials with high difference in strength and formability can be achieved. Further research to ensure process reliability and to improve the strength of the joint is required. One possible approach for this is the numerical investigation of the material flow during the joining process. Therefore, the definition of process parameters for the finite element model is necessary. A big impact on the quality of the results has the accuracy of the used friction values. As established testing methods are not suitable for modeling the rather complex tribological system between the joining partners of the shear-clinching process, an innovative testing method is needed. Studies in the field of sheet-bulk metal forming already demonstrated the applicability of the ring compression test for sheet metals. This paper presents a concept for the adaption of the ring compression test to the specific needs of the investigated shear-clinching process. The numerical identification of the friction coefficients is validated by experimental data and first results are qualified by experimental and simulative shear-clinching joints.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

The challenge of assessing the market value of private companies using a standardised combination method for tax purposes--Lessons to be learnt from past experience - Müller, Jens (European Accounting Review)
When taxes on capital or wealth are levied, in most countries companies have to be assessed in terms of their market value (MV). Estimating the MV of private companies for tax purposes is a challenging task for tax authorities as MVs are not available. In this study, I empirically analyse to what extent an accounting-based tax valuation method for private companies, a simplified residual income model, succeeds in matching the MV. I refer to the mandatory Standardised Combination Model that is a special case of methods commonly used in several countries. In the absence of market prices for private companies, I use a sample of small German public companies as a proxy. I validate this approach using a sensitivity analysis that involves matching the sample of public companies with that of private companies. The results imply that the mandatory Standardised Combination Model leads to a severe unequal treatment not only between public and private companies but also among private companies across and within industries. Furthermore, I simulate the effects of variation in the key parameters and highlight their impact on the approximation quality of the Standardised Combination Method. The findings are relevant to tax reform discussions as well as to tax policy-makers and practitioners in many countries.
Keywords: Challenge of Assessing; Tax Purposes

Augmented reality in informal learning environments: A field experiment in a mathematics exhibition - Sommerauer, Peter; Müller, Oliver (Computers and Education)
Keywords: Augmented reality; Cognitive theory of multimedia learning; Field experiment; Informal learning; Museum

Towards Online Source Counting in Speech Mixtures Applying a Variational EM for Complex Watson Mixture Models - Drude, Lukas; Chinaev, Aleksej; Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (14th International Workshop on Acoustic Signal Enhancement (IWAENC 2014))
This contribution describes a step-wise source counting algorithm to determine the number of speakers in an offline scenario. Each speaker is identified by a variational expectation maximization (VEM) algorithm for complex Watson mixture models and therefore directly yields beamforming vectors for a subsequent speech separation process. An observation selection criterion is proposed which improves the robustness of the source counting in noise. The algorithm is compared to an alternative VEM approach with Gaussian mixture models based on directions of arrival and shown to deliver improved source counting accuracy. The article concludes by extending the offline algorithm towards a low-latency online estimation of the number of active sources from the streaming input data.
Keywords: Accuracy; Acoustics; Estimation; Mathematical model; Soruce separation; Speech; Vectors; Bayes methods; Blind source separation; Directional statistics; Number of speakers; Speaker diarization

A series of amide functionalized isoreticular metal organic frameworks - Keceli, E.; Hemgesberg, M.; Grünker, R.; Bon, V.; Wilhelm, C.; Philippi, T.; Schoch, Roland; Sun, Y.; Bauer, Matthias; Ernst, S.; Kaskel, S.; Thiel, Werner R. (Microporous and Mesoporous Materials)
Keywords: Mechanics of Materials; Condensed Matter Physics; General Materials Science; General Chemistry

Hardness of approximation for quantum problems - Gharibian, Sevag; Kempe, Julia (Quantum Information & Computation)
The polynomial hierarchy plays a central role in classical complexity theory. Here, we define a quantum generalization of the polynomial hierarchy, and initiate its study. We show that not only are there natural complete problems for the second level of this quantum hierarchy, but that these problems are in fact hard to approximate. Using the same techniques, we also obtain hardness of approximation for the class QCMA. Our approach is based on the use of dispersers, and is inspired by the classical results of Umans regarding hardness of approximation for the second level of the classical polynomial hierarchy [Umans, FOCS 1999]. The problems for which we prove hardness of approximation for include, among others, a quantum version of the Succinct Set Cover problem, and a variant of the local Hamiltonian problem with hybrid classical-quantum ground states.
Keywords: Hardness of approximation; polynomial time hierarchy; succinct set cover; quantum complexity

The use of radiation-cured adhesives on adhesive stud assembly process - Meschut, Gerson; Süllentrop, Sebastian (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Innovative and Highly Productive Joining Technologies for Multi-Material Lightweight Car Body Structures - Meschut, G.; Janzen, V.; Olfermann, T. (Journal of Materials Engineering and Performance)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Basic Investigations of Non-Pre-Punched Joining by Forming of Aluminium Alloy and High Strength Steel with Shear-Clinching Technology - Merklein, Marion; Meschut, Gerson; Müller, Martin; Hörhold, Réjane (Key Engineering Materials)
Facing a decreasing amount of resources on the one hand and an increasing demand for comfort on the other, more and more attention is being paid to sustainability and care for the environment. Particularly in the automotive sector, lightweight design principles continue to prosper rapidly. As a result, adjusted materials for different applications were developed. Due to the formation of intermetallic phases, most multi-material mixes cannot be welded and require adapted joining technologies. Mechanical joining technologies such as self-piercing riveting and mechanical clinching have proven effective methods of joining lightweight materials like aluminium and ductile steels. New high-strength steels are increasingly used in crash-sections, where limited deformation under impact load is required. These hot stamped steels have a very low elongation at break and therefore a low formability. Currently there is no joining by forming technology without pre-punching available using these grades of steels on die-side. The newly developed shear-clinching process is one possible method of joining this kind of material without additional elements. The fundamental idea of shear-clinching is a single-stage process in which pre-punching of the die-side material is performed by indirect shear-cutting and subsequent forming of the upper layer into this hole. This would immensely enlarge the application segment of mechanical clinching even if hot stamped steels are positioned on die-side. Fundamental studies are required to ensure process reliability and it is necessary to break down the joining process into fragments, like pre-punching and clinching with pre-punched sheet, and superpose them to form the combined procedure shear-clinching. This paper presents a detailed investigation of the sub-process clinching with pre-hole.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Determinants of market beta: the impacts of firm-specific accounting figures and market conditions - Schlueter, Tobias; Sievers, Sönke (Review of Quantitative Finance and Accounting (VHB-JOURQUAL 3 Ranking B))
This article examines and extends research on the relation between the capital asset pricing model market beta, accounting risk measures and macroeconomic risk factors. We employ a beta decomposition approach that nests competing models with different business risk proxies and allows to frame cross-model comparison. Because model tests require estimated independent variables resulting in measurement error, we empirically estimate three comparable model specifications with instrumental variable estimators and for the first time provide thorough instrument diagnostics in this setting. Correcting for the heretofore neglected weak instruments problem we find that growth risk (i.e., the risk of firm sales variations that are inconsistent with the market wide trends), is the business risk that explains cross-sectional variations in market beta best.
Keywords: CAPM; Cost of capital; Accounting beta; Intrinsic business risk; Growth risk; Instrumental variables

On the assessment of attitudes towards the study process and the university: Attitudes towards the Study Environment Questionnaire (ASEQ) - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
The purpose of the research was to develop and validate an instrument for the assessment of attitudes towards the study environment in higher education contexts. The questionnaire is designed to measure students' attitudes towards two particular objects: the university (or Higher Education Institution) and the process of studying. Five studies at two different universities were conducted to develop and validate the Attitudes towards the Study Environment Questionnaire (ASEQ). In total, 1640 students filled in the questionnaire. Reliability tests and exploratory factor analysis as well as confirmatory factor analysis showed satisfactory psychometric characteristics of the ASEQ. Each part of the questionnaire is internally consistent and construct validity of the scales is supported by correlations with other constructs as assumed by current theories: Positive attitudinal constructs (normative behavior, autonomy, joy, self-efficacy, and task value) are positively related to intrinsic motivation and the expected study performance while anxiety is negatively related to these constructs. Since attitudes towards the study situation are connected to student engagement and motivation, the study contributes to the theory of student learning by providing a validated instrument to assess attitudes. Thus, the ASEQ can support further research on student performance and development by providing an instrument for the hitherto neglected but nonetheless extremely relevant domain of attitudes. Also, the questionnaire can be used as a diagnostic instrument for higher education faculty and administration to trace students' attitudinal development over time - a factor of prime importance for student socialization during the introductory phase of studying.
Keywords: attitudes; teaching and learning; studying; higher education institution; theory of planned behavior; instrument development

Die Entwicklung studien-und hochschulbezogener Einstellungen an einer Wirtschaftsuniversität: eine qualitative Längsschnittstudie - Jenert, Tobias; Brahm, Taiga
Die vorliegende Untersuchung an der Universität St. Gallen soll Erkenntnisse über die Verläufe der Einstellungsveränderungen der Studierenden geben (vgl. Brahm & Jenert, 2012). Basierend auf der Theorie des geplanten Verhaltens (Ajzen & Fishbein, 1980) werden drei Forschungsfragen adressiert: (1) Gibt es typische Pfade der Einstellungsentwicklung? (2) Wie wird das normative Verhalten von Mitstudierenden und anderen Personen wahrgenommen? (3) Welche Erfahrungen beeinflussen die Entwicklung? Zur Beantwortung dieser Fragen wurde über das erste Studienjahr hinweg eine Interviewserie mit 13 Studierenden durchgeführt. Die Datenanalyse mithilfe grafischer Case Histories zeigt, dass die Einstellungen der Probanden über die Zeit differenzierter werden. Zudem gibt es Widersprüche zwischen den Einstellungen und dem wahrgenommenen normativen Verhalten. Dabei ist die Einstellungsentwicklung von konkreten Ereignissen geprägt und kann damit durch strukturelle Interventionen beeinflusst werden.
Keywords: student attitudes; theory of planned behaviour; Einstellungsentwicklung; student motivation

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part I: Ideal Excitation. - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Piezoelectric inertia motors, also known as ``stick--slip drives'', use the inertia of a body to drive it in small steps by means of a friction contact. While these steps are classically assumed to involve stiction and sliding, the motors can also operate in ``slip--slip'' mode without any phase of static friction. This contribution provides a systematic investigation and performance comparison of different stick--slip and slip--slip modes of operation. Different criteria for comparing the motional performance of inertia motors are defined: Steady state velocity, smoothness of motion, and start-up time. Using the example of a translational inertia motor excited by an ideal displacement signal, it is found that the maximum velocity reachable in stick--slip operation is limited principally, while continuous slip--slip operation allows very high velocities. For the investigated driving signals, the motor velocity is proportional to the square root of the actuator stroke. The motor performance with these ideal signals defines an upper boundary for the performance of real motors.
Keywords: Inertia motor; Stick--slip drive; Mode of operation; Performance indicator; Velocity maximization; Actuator stroke

Investment distortions and the value of the government's tax claim - Kreutzmann, Daniel; Sievers, Sönke; Mueller, Christian (Applied Financial Economics (VHB-JOURQUAL 3 Ranking C))
This study integrates the government in the context of company valuation. Our framework allows to analyze and to quantify the risk-sharing effects and conflicts of interest between the government and the shareholders when firms follow different financial policies. We provide novel evidence that firms with fixed future levels of debt might invest more than socially desirable. Economically, this happens if the gain in tax-shields is big enough to outweigh the loss in the unlevered firm value. Our findings have implications for the practice of investment subsidy programs provided by the government to avoid fostering investments beyond the socially optimal level.
Keywords: corporate tax claim; company valuation; optimal investment; cost of capital

GMM-based significance decoding - Abdelaziz, Ahmed H.; Zeiler, Steffen; Kolossa, Dorothea; Leutnant, Volker; Haeb-Umbach, Reinhold (Acoustics, Speech and Signal Processing (ICASSP), 2013 IEEE International Conference on)
The accuracy of automatic speech recognition systems in noisy and reverberant environments can be improved notably by exploiting the uncertainty of the estimated speech features using so-called uncertainty-of-observation techniques. In this paper, we introduce a new Bayesian decision rule that can serve as a mathematical framework from which both known and new uncertainty-of-observation techniques can be either derived or approximated. The new decision rule in its direct form leads to the new significance decoding approach for Gaussian mixture models, which results in better performance compared to standard uncertainty-of-observation techniques in different additive and convolutive noise scenarios.
Keywords: Bayes methods; Gaussian processes; convolution; decision theory; decoding; noise; reverberation; speech coding; speech recognition; Bayesian decision rule; GMM; Gaussian mixture models; additive noise scenarios; automatic speech recognition systems; convolutive noise scenarios; decoding approach; mathematical framework; reverberant environments; significance decoding; speech feature estimation; uncertainty-of-observation techniques; Hidden Markov models; Maximum likelihood decoding; Noise; Speech; Speech recognition; Uncertainty; Uncertainty-of-observation; modified imputation; noise robust speech recognition; significance decoding; uncertainty decoding

Using the turbo principle for exploiting temporal and spectral correlations in speech presence probability estimation - Vu, Dang Hai Tran; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2013))
In this paper we present a speech presence probability (SPP) estimation algorithmwhich exploits both temporal and spectral correlations of speech. To this end, the SPP estimation is formulated as the posterior probability estimation of the states of a two-dimensional (2D) Hidden Markov Model (HMM). We derive an iterative algorithm to decode the 2D-HMM which is based on the turbo principle. The experimental results show that indeed the SPP estimates improve from iteration to iteration, and further clearly outperform another state-of-the-art SPP estimation algorithm.
Keywords: correlation methods; estimation theory; hidden Markov models; iterative methods; probability; spectral analysis; speech processing; 2D HMM; SPP estimates; iterative algorithm; posterior probability estimation; spectral correlation; speech presence probability estimation; state-of-the-art SPP estimation algorithm; temporal correlation; turbo principle; two-dimensional hidden Markov model; Correlation; Decoding; Estimation; Iterative decoding; Noise; Speech; Vectors

External governance outcome and microfinance success - Uhde, André; Müller, Oliver (International Journal of Monetary Economics and Finance)
Employing a Hausman–Taylor instrument variable (HT–IV) estimator to data from 558 microfinance institutions (MFIs) in 80 developing countries for the period from 2002 to 2007, this paper provides empirical evidence for a positive impact of a country's external governance quality and outcome on local microbanks' economic success in terms of profitability and sustainability. Evidence as well suggests a negative relationship between external governance and the microbanks' social success measured by the depth of outreach. In this context, our analysis reveals that a country's political stability, governance effectiveness, regulatory quality and rule of law are significant key elements of external governance affecting the MFIs' functional performance. Moreover, results from sensitivity analyses indicate that the relationship between external governance quality and microfinance functional performance significantly depends on the microbanks' business concepts, their lending methodologies and sources of funding.
Keywords: microfinance; external governance; economic success; social success; developing countries; profitability; sustainability; microbanks; outreach; political stability; governance effectiveness; regulatory quality; rule of law; governance quality; lending methodologies; funding sources

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Kosi, Urska; Koren, Jerney; Valentincic, Aljosa
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.
Keywords: private firms; voluntary audit; cost of debt; self-selection bias; lemon problem

Educating attention: recruiting, maintaining, and framing eye contact in early natural mother-infant interactions - Nomikou, Iris; Rohlfing, Katharina; Szufnarowska, Joanna (Interaction Studies)
In a longitudinal naturalistic study, we observed German mothers interacting with their infants when they were 3 and 6 months old. Pursuing the idea that infants’ attention is socialized in everyday interactions, we explored whether eye contact is reinforced selectively by behavioral modification in the input provided to infants. Applying a microanalytical approach focusing on the sequential organization of interaction, we explored how the mother draws the infant’s attention to herself and how she tries to maintain attention when the infant is looking at her. Results showed that eye contact is reinforced by specific infant-directed practices: interrogatives and conversational openings, multimodal stimulation, repetition, and imitation. In addition, these practices are contingent on the infant’s own behavior. By comparing the two data points (3 and 6 months), we showed how the education of attention evolves hand-in-hand with the developing capacities of the infant.
Keywords: interactional adaptation; multimodal input; social learning; ecology of attention; eye contact

Innovative joining technologies for multi-material structures - Meschut, G.; Hahn, O.; Janzen, V.; Olfermann, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Korrosionsverhalten binärer Magnesium-Zink-Legierungen in salzhaltigen Medien - Hoyer, Kay-Peter; Angrisani, Gian Luigi; Klose, Christian; Bach, Friedrich-Wilhelm; Hassel, Thomas (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Einfluss der Oberflächenbehandlung auf das Korrosionsverhalten von Magnesiumlegierungen - Hoyer, Kay-Peter; Hassel, Thomas; Bach, Friedrich-Wilhelm (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Processing Multilingual Customer Contacts via Social Media - Geierhos, Michaela; Lee, Yeong Su; Bargel, Matthias (Multilingual Resources, Multilingual Applications: Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we will describe a new approach to customer interaction management by integrating social networking channels into existing business processes. Until now, contact center agents still read these messages and forward them to the persons in charge of customer’s in the company. But with the introduction of Web 2.0 and social networking clients are more likely to communicate with the companies via Facebook and Twitter instead of filling data in contact forms or sending e-mail requests. In order to maintain an active communication with international clients via social media, the multilingual consumer contacts have to be categorized and then automatically assigned to the corresponding business processes (e.g. technicalservice, shipping, marketing, and accounting). This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer relationship management.
Keywords: Classification of Multilingual Customer Contacts; Contact Center Application Support; Social Media Business Integration

Friction in wheel--rail contact: A model comprising interfacial fluids, surface roughness and temperature - Tomberger, Christoph; Dietmaier, Peter; Sextro, Walter; Six, Klaus (Wear)
A profound description of friction in wheel--rail contact plays an essential role for optimization of traction control strategies, as input quantity for railway simulations in general and for the estimation of wear and rolling contact fatigue. A multitude of wheel--rail contact models exists, however, traction--creepage curves obtained from measurements show quantitative and qualitative deviations. There are several phenomena which influence the traction--creepage characteristics: Mechanisms resulting from surface roughness, frictional heating or the presence of interfacial fluids can have a dominating influence on friction. In this paper, a new wheel--rail contact model, accounting for these influential parameters, will be presented. The presented model accounts for the interaction of an interfacial fluid model for combined boundary and mixed lubrication of rough surfaces with a wheel--rail contact model that additionally accounts for frictional heating. A quantitative comparison with measurements found in the literature is not conducted, since the exact conditions of the measurements are mostly unknown and parameters can easily be adjusted to fit the measurements. Emphasis is placed on the qualitative behavior of the model with respect to the measurements and good agreement is found. The dependence of the maximum traction coefficient on rolling velocity, surface roughness and normal load is studied under dry and water lubricated conditions.
Keywords: Wheel--rail contact; Rolling contact; Friction; Interfacial fluid; Lubrication; Surface roughness; Contact temperature

Language Does Something: Body Action and Language in Maternal Input to Three-Month-Olds - Nomikou, Iris; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)
Keywords: acoustic packaging; mother-child interaction; social learning; multimodal grounding in input; ecology of interactions; synchrony

Synthesis of highly stable magnesium fluoride suspensions and their application in the corrosion protection of a Magnesium alloy - Waltz, Florian; Swider, Mark A.; Hoyer, Kay-Peter; Hassel, Thomas; Erne, Martin; Möhwald, Kai; Adlung, Matthias; Feldhoff, Armin; Wickleder, Claudia; Bach, Friedrich-Wilhelm; Behrens, Peter (Journal of Materials Science)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Negotiating identities through pronouns of address in an immigrant community - Liebscher, Grit; Dailey-O’Cain, Jennifer; Müller, Mareike; Reichert, Tetyana (Pragmatics. Quarterly Publication of the International Pragmatics Association (IPrA))
This article investigates forms of address, in particular the T/V distinction in German, in conversational interviews with German-speaking immigrants to English-speaking Canada and their descendants. From among 77 interviews conducted in two urban areas in Canada, we discuss instances of both the interactional use of and metalinguistic comments on forms of address. Our analysis is largely guided by conversation analysis and interactional sociolinguistics (e.g. Goodwin & Heritage 1990). Using Clyne, Norrby and Warren’s (2009) model of address as a backdrop, we investigate the construction of group identity and group socialization through the lens of positioning theory (e.g. van Langenhove & Harré 1993; Dailey-O’Cain & Liebscher 2009). This combination of analytical tools can explain shifts in both usage of and attitudes toward the T/V distinction that cannot be explained through language attrition arguments alone.
Keywords: Forms of address; T/V distinction; Du vs. Sie; Conversation analysis; Language attitudes; Interviews; German in Canada; Migration studies; North American migration

Zugänge zum Begriff der Lernkultur: Eine Systematisierung auf Basis kultur-und lerntheoretischer Überlegungen - Jenert, Tobias; Gebhardt, Anja
"Lernkultur" wird als Begriff häufig gebraucht und fast ebenso häufig definiert  das gilt für den betrieblichen Kontext ebenso wie für die Bereiche der Schul-, Hochschul-, Berufs- und Erwachsenenbildung (z. B. Wulf, Althans, Blaschke, Ferrin, Göhlich, Jörissen, Mattig et al., 2007; Jenert, Zellweger Moser, Dommen & Gebhardt, 2009; Kirchhöfer, 2004; Erpenbeck & Sauer, 2000). Trotz der grossen Aufmerksamkeit, die der Begriff in den letzten zwei Jahrzehnten erfahren hat, kann man nicht von einem in sich geschlossenen Forschungsprogramm sprechen. Die Zugänge zum Phänomenbereich Lernkultur sind ebenso vielfältig wie die hinter einzelnen Ansätzen stehenden Lernkulturkonstrukte. Den Autoren ist keine Publikation bekannt, welche unterschiedliche Ansätze der Lernkulturforschung systematisch aufarbeitet. Eine wichtige Referenzquelle ist der Bericht von Kuh und Whitt (1988) "The Invisible Tapestry: Culture in American Colleges and Universities". Ausgehend von einer fundierten Übersicht zu unterschiedlichen Zugängen zum Kulturbegriff (oft in starker Anlehnung an die Organisationskulturforschung (vgl. Allaire & Firsirotu, 1984)) stellen die Autoren ein Rahmenmodell zur Analyse von Hochschulkulturen vor (Kuh und Whitt, 1988, S. 56). Diese Arbeit erweist sich für ein besseres Verständnis unter-schiedlicher Zugänge zum Lernkulturbegriff als aufschlussreich, weil im Kontext Hoch-schule zwangsweise viele Aspekte des Lernens und Lehrens angesprochen werden. Allerdings fokussiert auch dieser Bericht nicht das Konstrukt der Lernkultur und bietet damit nur einen Ausgangspunkt für die Identifizierung unterschiedlicher Zugänge.
Keywords: Lernkultur; learning culture; culture theory; approaches to learning culture; culture of learning

Various Aspects of the Placement of a Piezoelectric Material in Composite Actuators, Motors, and Transducers - Hemsel, Tobias; Lierk, Ernst Günther; Littmann, Walter; Morita, Takeshi (Journal of Korean Physical Society)
Piezoelectric materials find wide application in technical systems. Most often, a combination of piezoelectric and other materials is advantageous. The position and the amount of the piezoelectric material within the overall system depends on various aspects like maximum mechanical output to the load, maximum electromechanical efficiency of the system, maximum utilization of the piezoelectric material, minimum self-heating of the piezoelectric material, and controllability of the system, which might be key aspects for the optimisation of the system design. For a composite longitudinal vibrator (bolted Langevin transducer), which is a base for many technical applications, this contribution shows in detail, how above mentioned aspects depend on the position and volume of the piezoelectric material related to the mode shape.
Keywords: Bolted Langevin transducer; Optimum placement of piezoelectric ceramics

Enhancing implicit change detection through action. - Tseng, Philip; Tuennermann, Jan; Roker-Knight, Nancy; Winter, Dorina; Scharlau, Ingrid; Bridgeman, Bruce (Perception)
Implicit change detection demonstrates how the visual system can benefit from stored information that is not immediately available to conscious awareness. We investigated the role of motor action in this context. In the first two experiments, using a one-shot implicit change detection paradigm, participants responded to unperceived changes either with an action (jabbing the screen at the guessed location of a change) or with words (verbal report), and sat either 60 cm or 300 cm (with a laser pointer) away from the display. Our observers guessed the locations of changes at a reachable distance better with an action than with a verbal judgment. At 300 cm, beyond reach, the motor advantage disappeared. In experiment 3, this advantage was also unavailable when participants sat at a reachable distance but responded with hand-held laser pointers near their bodies. We conclude that a motor system specialized for real-time visually guided behavior has access to additional visual information.
Keywords: implicit change detection; action perception; visual system; perceptual judgment; verbal fluency; Analysis of Variance; Awareness; Female; Humans; Male; Psychomotor Performance; Random Allocation; Reaction Time; Visual Perception; Visual Memory; Visual Stimulation; Implicit Memory; Judgment; Perceptual Discrimination

Sampling methods for shortest vectors, closest vectors and successive minima - Blömer, Johannes; Naewe, Stefanie (Theoretical Computer Science)
Keywords: Geometry of numbers; Lattices; Shortest vectors

Zusammenhänge zwischen der Fähigkeit zur Perspektivenübernahme und dem Textverstehen im Vor- und Grundschulalter - Buhl, Heike M.; Möller, Franziska; Oebser, Manuela; Stein, Freia; Noack, Peter (Diskurs Kindheits- und Jugendforschung)
Im vorliegenden Beitrag wird der Zusammenhang zwischen der Fähigkeit zur Perspektivenübernahme und sinnverstehendem Lesen dargestellt. Auf der Grundlage von Arbeiten zum Textverstehen sowie zu Perspektivenübernahme und Theory of Mind wurde ein positiver Zusammenhang zwischen Perspektivenübernahmefähigkeit und Textverstehensleistung erwartet. Diese Hypothese wurde an zwei Stichproben unterschiedlichen Alters geprüft: In der ersten Studie beantworteten 37 Vorschulkinder Fragen zu vorgelesenen Geschichten sowie Perspektivenübernahme-Aufgaben. Zwischen den Bereichen fand sich eine deutliche positive Korrelation, die bei Kontrolle der Intelligenz erhalten blieb. An der zweiten Studie nahmen 69 Grundschulkinder der dritten Jahrgangsstufe teil, die Texte lasen und Aufgaben dazu wie auch zur Perspektivenübernahme bearbeiteten. In dieser Stichprobe fand sich der erwartete Zusammenhang ausschließlich in der Teilgruppe der guten Leser. Er blieb bei Kontrolle der Intelligenz erhalten. Die Ergebnisse werden auch in Hinblick auf die Förderung der Lesekompetenz diskutiert.
Keywords: Textverstehen; Lesekompetenz; Perspektivenübernahme; Theory of Mind; Kindesalter

Verlässlichkeitorientierte Technologiebewertung innovativer Aktortechnologien am Beispiel von Formgedächtnislegierungen - Müller, Thomas; Schiedeck, Florian; Hemsel, Tobias (2. Tagung des DVM -- Arbeitskreis Zuverlässigkeit mechatronischer und adaptronischer Systeme: Absicherung der Systemzuverlässigkeit, Koblenz)
EN: Although the use of new actuator technologies is quite enthusiastic, the realization of innovative systems based on these principles fails because of doubts in dependability. Until now, new working principles for actuators have not been systematically investigated in the means of dependability. Therefore we developed a proceeding for a dependability-oriented evaluation of technologies. This is shown in the case of shape memory alloy actuators. DE: Die Realisierung von Systemen mittels innovativer Aktortechnologien scheitert oftmals an der Skepsis gegenüber der Verlässlichkeit (Vertrauen in die zuverlässige und sichere Funktionalität der Technologie). Diese liegt darin begründet, dass neue Aktortechnologien bzw. die Integration von innovativen physikalischen Wirkprinzipen innerhalb neuer Aktorkonzepte bisher noch nicht systematisch im Kontext der Verlässlichkeit untersucht werden. Daher haben wir ein Vorgehen zur verlässlichkeitsorientierten Technologiebewertung entwickelt. Neben der detaillierten Darstellung des Vorgehensmodells wird es exemplarisch anhand von Formgedächtnislegierungen zur Entwicklung innovativer Antriebslösungen angewendet.
Keywords: EN: Dependability; Reliability; Evaluation of Technology; Actuators; Shape Memory Alloys DE: Verl{\

Kooperation, Kompetenz und Kontinuität: Grundlagen innovativer Fach-Communities im Mittelstand - Jenert, Tobias (Wirtschaftspsychologie)
Der Beitrag beschreibt die Potenziale informeller Mitarbeiter-Communities für die Innovationsfähigkeit kleiner und mittlerer Unternehmen (KMU). Innovationsmanagement bezieht sich in der Regel auf grosse Unternehmen. Die speziellen Bedürfnisse und Möglichkeiten von KMU werden dabei oftmals vernachlässigt. Auf Basis einer Fallstudie werden daher Gestaltungsmöglichkeiten für innovationsfreundliche Arbeitskontexte in kleinen und mittleren Betrieben herausgearbeitet. Im Mittelpunkt der Analyse stehen Kriterien, die kritisch für die Entstehung und den Fortbestand informeller Innovationsnetzwerke innerhalb formeller Organisationsstrukturen sind. Die Studie greift auf Erkenntnisse der Kreativitäts- und der Lernforschung zurück und bezieht sich explizit auf den Community of Practice-Ansatz. Abschliessend werden die Grenzen eines "Managements" innovativer Mitarbeiternetzwerke diskutiert und Möglichkeiten der Gestaltung von Arbeitskontexten vorgestellt.
Keywords: Innovation; Community of Practice; KMU

Blind Acoustic Beamforming Based on Generalized Eigenvalue Decomposition - Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
Maximizing the output signal-to-noise ratio (SNR) of a sensor array in the presence of spatially colored noise leads to a generalized eigenvalue problem. While this approach has extensively been employed in narrowband (antenna) array beamforming, it is typically not used for broadband (microphone) array beamforming due to the uncontrolled amount of speech distortion introduced by a narrowband SNR criterion. In this paper, we show how the distortion of the desired signal can be controlled by a single-channel post-filter, resulting in a performance comparable to the generalized minimum variance distortionless response beamformer, where arbitrary transfer functions relate the source and the microphones. Results are given both for directional and diffuse noise. A novel gradient ascent adaptation algorithm is presented, and its good convergence properties are experimentally revealed by comparison with alternatives from the literature. A key feature of the proposed beamformer is that it operates blindly, i.e., it neither requires knowledge about the array geometry nor an explicit estimation of the transfer functions from source to sensors or the direction-of-arrival.
Keywords: acoustic signal processing; arbitrary transfer function; array signal processing; blind acoustic beamforming; direction-of-arrival; direction-of-arrival estimation; eigenvalues and eigenfunctions; generalized eigenvalue decomposition; gradient ascent adaptation algorithm; microphone arrays; microphones; narrowband array beamforming; sensor array; single-channel post-filter; spatially colored noise; transfer functions

Dichroic photo- and electroluminescence of oligo p-(phenylene vinylene) derivatives - Lauhof, Marcus W.; Benning, Stephan A.; Kitzerow, Heinz-Siegfried; Vill, Volkmar; Scheliga, Felix; Thorn-Csányi, Emma (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Spin-electronic devices with half-metallic Heusler alloys - Hütten, A.; Schmalhorst, J.; Thomas, A.; Kämmerer, S.; Sacher, Marc; Ebke, D.; Liu, N.-N.; Kou, X.; Reiss, G. (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Degradation of organic field-effect transistors made of pentacene - Pannemann, Ch.; Diekmann, T.; Hilleringmann, Ulrich (Journal of Materials Research)
This article reports degradation experiments on organic thin film transistors using the small organic molecule pentacene as the semiconducting material. Starting with degradation inert p -type silicon wafers as the substrate and SiO 2 as the gate dielectric, we show the influence of temperature and exposure to ambient air on the charge carrier field-effect mobility, on-off-ratio, and threshold-voltage. The devices were found to have unambiguously degraded over 3 orders of magnitude in maximum on-current and charge carrier field-effect mobility, but they still operated after a period of 9 months in ambient air conditions. A thermal treatment was carried out in vacuum conditions and revealed a degradation of the charge carrier field-effect mobility, maximum on-current, and threshold voltage.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Degradation of organic field-effect transistors made of pentacene - Pannemann, Ch.; Diekmann, T.; Hilleringmann, Ulrich (Journal of Materials Research)
This article reports degradation experiments on organic thin film transistors using the small organic molecule pentacene as the semiconducting material. Starting with degradation inert p -type silicon wafers as the substrate and SiO 2 as the gate dielectric, we show the influence of temperature and exposure to ambient air on the charge carrier field-effect mobility, on-off-ratio, and threshold-voltage. The devices were found to have unambiguously degraded over 3 orders of magnitude in maximum on-current and charge carrier field-effect mobility, but they still operated after a period of 9 months in ambient air conditions. A thermal treatment was carried out in vacuum conditions and revealed a degradation of the charge carrier field-effect mobility, maximum on-current, and threshold voltage.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Director reorientation of a side-chain liquid crystalline polymer under extensional flow - Cormier, Ryan J.; Schmidt, Claudia; Callaghan, Paul T. (Journal of Rheology)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Morphology and fluorescence quenching in photovoltaic samples containing fullerene and poly(p-phenylene-vinylene) derivatives - Röder, T; Kitzerow, Heinz-Siegfried; Hummelen, J.C (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Piezoelectric transformers - state of the art and development trends - Hemsel, Tobias; Littmann, Walter; Wallaschek, Jörg (Ultrasonics Symposium, 2002. Proceedings. 2002 IEEE)
Piezoelectric transformers are well known since the publication of some patent applications at the end of the 1950s. But until today their only business use lies in the field of backlighting systems for LCDs. Due to key features as light-weight, flatness, high step-up at low volume and high efficiency piezoelectric transformers should be usable in a much broader range of applications. This contribution returns to mind their operating principle, shows how to model and to develop such devices as well as give some aspects for development trends that will lead to further applications.
Keywords: piezoelectric devices; reviews; transformers; backlighting systems; flatness; high efficiency piezoelectric transformers; high step-up; light-weight; low volume; operating principle; piezoelectric transformers; Circuits; Costs; Electromagnetic devices; Electromagnetic fields; Mechanical energy; Piezoelectric materials; Power electronics; Switching frequency; Transformers; Vibrations

Strength difference in compression and tension and pressure dependence of yielding in elasto-plasticity - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

A finite element algorithm for parameter identification of material models for fluid saturated porous media - Mahnken, Rolf; Steinmann, P. (International Journal for Numerical and Analytical Methods in Geomechanics)
Keywords: Mechanics of Materials; Geotechnical Engineering and Engineering Geology; General Materials Science; Computational Mechanics

Finite element simulation for rock salt with dilatancy boundary coupled to fluid permeation - Mahnken, Rolf; Kohlmeier, M. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Parameter identification of gradient enhanced damage models with the finite element method - Mahnken, Rolf; Kuhl, Ellen (European Journal of Mechanics - A/Solids)
Keywords: General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; General Materials Science

A unified approach for parameter identification of inelastic material models in the frame of the finite element method - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

The identification of parameters for visco-plastic models via finite-element methods and gradient methods - Mahnken, Rolf; Stein, E (Modelling and Simulation in Materials Science and Engineering)
Keywords: Computer Science Applications; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Parameter identification for viscoplastic models based on analytical derivatives of a least-squares functional and stability investigations - Mahnken, Rolf; Stein, Erwin (International Journal of Plasticity)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Parameter identification for finite deformation elasto-plasticity in principal directions - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Aspects on the finite-element implementation of the Gurson model including parameter identification - Mahnken, Rolf (International Journal of Plasticity)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Partner orientation and speaker’s knowledge as conflicting parameters in language production - Buhl, Heike M. (Journal of Psycholinguistic Research)
Two parameters of language production, the partner model and the mentally represented knowledge about a spatial constellation, are investigated with respect to their influence on spatial reference. At issue is whether the verbally expressed point of view in route directions is primarily influenced by the needs of the partner or by the underlying mental representation of the speaker stemming from his or her own experience with an object. Two experiments in which participants (N 5 90) were asked to produce a set of route directions are reported. The experimental situation was such that the point of view of the speaker did not correspond to the point of view of the partner. The results show that more participants localize from their own point of view than from the point of view of the partner. Discussion centers on the fact that speakers do not always behave in a truly partner-oriented manner.
Keywords: language production; partner model; mental representation; spatial point of view; route direction

Rheology and nuclear magnetic resonance measurements under shear of sodium dodecyl sulfate/decanol/water nematics - Thiele, Thomas; Berret, J.-F.; Müller, Stefan; Schmidt, Claudia (Journal of Rheology)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science